2010
DOI: 10.1051/0004-6361/201015089
|View full text |Cite
|
Sign up to set email alerts
|

A sample of [C II] clouds tracing dense clouds in weak FUV fields observed byHerschel

Abstract: The [C ii] fine-structure line at 158 μm is an excellent tracer of the warm diffuse gas in the ISM and the interfaces between molecular clouds and their surrounding atomic and ionized envelopes. Here we present the initial results from Galactic observations of terahertz C + (GOT C+), a Herschel key project devoted to studying the [C ii] emission in the Galactic plane using the HIFI instrument. We used the [C ii] emission, together with observations of CO, as a probe to understand the effects of newly formed st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…In a preliminary study of [C ii], 12 CO, and 13 CO velocity components on 16 GOT C+ LOSs, Pineda et al (2010b) used PDR model calculations to constrain the strength of the FUV field to be mostly χ 0 = 1−10, over a wide range of H 2 volume densities, thus suggesting that most of the observed [C ii] emission associated with 12 CO and 13 CO is exposed to weak FUV radiation fields. A similar result, was obtained from PDR modeling of the [C ii] emission observed by COBE by Cubick et al (2008), suggesting that most of the [C ii] in our Galaxy originates in a clumpy medium exposed to an FUV field of χ 0 60.…”
Section: The Fuv Radiation Field Distribution In the Milky Waymentioning
confidence: 99%
See 1 more Smart Citation
“…In a preliminary study of [C ii], 12 CO, and 13 CO velocity components on 16 GOT C+ LOSs, Pineda et al (2010b) used PDR model calculations to constrain the strength of the FUV field to be mostly χ 0 = 1−10, over a wide range of H 2 volume densities, thus suggesting that most of the observed [C ii] emission associated with 12 CO and 13 CO is exposed to weak FUV radiation fields. A similar result, was obtained from PDR modeling of the [C ii] emission observed by COBE by Cubick et al (2008), suggesting that most of the [C ii] in our Galaxy originates in a clumpy medium exposed to an FUV field of χ 0 60.…”
Section: The Fuv Radiation Field Distribution In the Milky Waymentioning
confidence: 99%
“…Kaufman et al (1999) showed that the ratio of [C ii] to CO is a good tracer of the strength of the FUV field in the galaxy. Using this line ratio in a sample of 16 LOSs, Pineda et al (2010b) found that most of the dense PDRs have FUV fields lower than 100 times the interstellar FUV field. With the complete GOT C+ survey, we can use the [C ii]/CO ratio to trace the strength of the FUV radiation field over the entire Galactic disk.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we use the [C ii] and CO data for 354 lines of sight Pineda et al (2010Pineda et al ( , 2013 toward the inner Galaxy in the longitude range l = 270…”
Section: Got C+ Survey Datamentioning
confidence: 99%
“…Our sample is made of relatively metal-rich spiral galaxies for which CO should be a more reliable tracer of the total molecular content. Still, some dark gas can also be found in the Milky Way (Grenier et al 2005;Langer et al 2010;Pineda et al 2010;Velusamy et al 2010;Planck Collaboration 2011). However, theoretical models suggest that for a given mean attenuation, the fraction of dark gas remains constant (Wolfire et al 2010).…”
Section: Dark Gasmentioning
confidence: 99%